121k views
0 votes
Can someone help ASAP

Can someone help ASAP-example-1
User Sepisoad
by
5.1k points

1 Answer

3 votes

Answer:

There's only one answer, and that's x=0.

Explanation:

Step 1: Simplify both sides of the equation.

3(3x−1)=6x−3

(3)(3x)+(3)(−1)=6x+−3(Distribute)

9x+−3=6x+−3

9x−3=6x−3

Step 2: Subtract 6x from both sides.

9x−3−6x=6x−3−6x

3x−3=−3

Step 3: Add 3 to both sides.

3x−3+3=−3+3

3x=0

Step 4: Divide both sides by 3.


(3x)/(3)=
(0)/(3)

x=0

hope this helps

User Elrobis
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.